Scalable Electrochemical Transition‐Metal‐Free Dehydrogenative Cross‐Coupling Amination Enabled Alkaloid Clausines Synthesis - Zhang, Pan; Li, Baoying; Niu, Liwei; Wang, Ling; Zhang, Guofeng; Jia, Xiaofei; Zhang, Guoying; Liu, Siyuan; Ma, Li; Gao, Wei; Qin, Dawei; Chen, Jianbin (Advanced synthesis & catalysis, 2020)
Reported herein is an environmentally benign electrochemical C−H bond dehydrogenative amination protocol for the construction of privileged carbazole moiety with broad generality. Preliminary mechanistic investigations implied a radical reaction pathway. Compared with traditional ionic routes, the scalable transition‐metal and exogenous‐oxidant free strategy highlighted the green and sustainable nature of this method.